Factors affecting the quality of mathematics teaching and learning of high school students in the 4th grade in Savannakhet province: https://doi.org/10.69692/SUJMRD100191 - PHOMMALANGSY, Phouvong; PHONESAY, Latsamy; SAIYASONE, Phoulatsamai; PHIMMASONE, Xayaphone; LUANGSENA, Phanmaha (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The purpose of this research is to examine the factors that affect the quality of learning and teaching mathematics of 4th grade students in Savannakhet province. The sample group included the 4th grade students and natural science teachers with a total number of 434. The data was analyzed by SPSS program and Microsoft Excel to calculate frequency, percentage, standard deviation, CV and content analysis. The results of the research are as follows: The results of the analysis of the factors that affect the quality of teaching mathematics the most according to the students' ideas are curriculum by average value of 3.58, which means that the curriculum is suitable with the current learning standards at a low level, followed by the factors of teachers and family with an average 3.57 and 3.52 respectively. The results of the analysis of the factors that affect the quality of teaching mathematics according to the teachers' ideas in general are at good levels and when considering each aspect, it is found that the factor that affect the most is the teacher with an average of 3.82, followed by the curriculum and teaching aids with an average of 3.81 and 3.80 respectively. The results of the analysis of teachers' and students' opinions toward the improvement of the quality of mathematics teaching are: paying more attention to study of students covering 28.65%; teaching methods consistently with the current situations, covering 15.63%, giving opportunities for students to participate in learning more covering 15.71%, and organizing a program to promote those who are good at learning and help weak students covering 12 .50% respectively.